POLIMORFISME PRIMER RAPD PADA TANAMAN JAMBU METE ASAL TIGA KABUPATEN DI SULAWESI TENGGARA - Mirza Arsiaty Arsyad; I Irwan; Dirvamena Boer; Yuni Fitri Cahyaningsih; Siti Halimah Larekeng; I Iswanto (JURNAL GALUNG TROPIKA, 2022)
Southeast Sulawesi is one of the largest producers of cashew commodities in Indonesia, which has an essential meaning in the world of trade. Determination of the polymorphism of a primer is the first step in conducting genetic diversity studies to obtain genetic information about a species. This study aims to determine the polymorphic RAPD primers to be used in the analysis of the genetic diversity of cashew in three districts in Southeast Sulawesi. The study used 20 RAPD primers to amplify cashew DNA samples and obtained three RAPD primers (OPA-15, OPP-08, and OPC-11 primers) which showed polymorphic bands in the DNA samples used. The three RAPD primers obtained have the potential to be used in genetic studies of cashew originating from Southeast Sulawesi.